Have one's view of the important overshadowed by the trivial: chronic progressive external ophthalmoplegia combined with unilateral facial nerve injury: a case report and literature review - Feng, Ziyang; Lai, Rui; Wei, Jia; Liu, Xuan; Chen, Xueqin; Liu, Yangsicheng; Qin, Wenxin; Qin, Xiude; Kong, Fanxin (Frontiers in Neurology, 2024)
Chronic progressive external ophthalmoplegia (CPEO) is a mitochondrial encephalomyopathy that is characterized by progressive ptosis and impaired ocular motility. Owing to its nonspecific clinical manifestations, CPEO is often misdiagnosed as other conditions. Herein, we present the case of a 34-year-old woman who primarily presented with incomplete left eyelid closure and limited bilateral eye movements. During the 6-year disease course, she was diagnosed with myasthenia gravis and cranial polyneuritis. Finally, skeletal muscle tissue biopsy confirmed the diagnosis. Biopsy revealed pathological changes in mitochondrial myopathy. Furthermore, mitochondrial gene testing of the skeletal muscle revealed a single chrmM:8469-13447 deletion. In addition, we summarized the findings of 26 patients with CPEO/Kearns–Sayre syndrome who were misdiagnosed with other diseases owing to ocular symptoms. In conclusion, we reported a rare clinical case and emphasized the symptomatic diversity of CPEO. Furthermore, we provided a brief review of the diagnosis and differential diagnosis of the disease.